Negative Poisson ratio based on textiles knitting fabric manufacturing process and mechanical properties: A review - Mohmmed, Ramadan; Mohamed Ahmed, Hasabo Abdelbagi; Cimilli Duru, Sena; Navidfar, Amir; Trabzon, Levent (SAGE Publications, 2025)
This paper reviews the advancements and potentials in Knitted Negative Poisson Ratio (NPR) materials, including warp-knitted, weft-knitted, and three-dimensional (3D) knitted structures. The review includes 10 sections the following order: a general introduction, defection of the NPR, the auxetic textile fabrics, warp and weft knitted, the 3D, the mechanical properties of auxetic knitted structure, advantages and drawbacks, and the future trends. However, research on knitted textile structures with Negative Poisson Ratio is limited in the literature so far. This type of material with unusual properties and 3D negative stiffness textile structure has been of interest for fundamental research, and engineering applications. Nonetheless, there is a need for a systematic study of their structural design and manufacturing process and their performance for further exploitation. Among different design structures, various structures have been designed and made to show the properties of (NPR). These negative Poisson ratio textiles knitted structures will enable new applications such as vibration isolation for transportation, defense Industries, aerospace, biomedical, sports industries, geotextile, construction, and many more high-value-added and innovative products.